Fostering Character and Digital Literacy via Student-Led Video Production in Child Islamic Boarding Schools - Taufikin Taufikin; Habib Badawi; Moses Adeleke Adeoye; Mowafg Abrahem Masuwd (SYAMIL: Journal of Islamic Education, 2025)
Digital transformation in Islamic education necessitates innovative pedagogical strategies that honor religious values while equipping students with 21st-century skills. Within this context, pesantren””Islamic boarding schools rooted in Qur’anic memorization and character formation””face the challenge of integrating modern tools without compromising their core traditions. This study aims to explore how student-led video content creation fosters character development and digital literacy among elementary-aged students at Pesantren Anak-anak Tahfidzul Qur’an Raudlatul Falah (PPATQ RF), Central Java, Indonesia. Using a qualitative case study design, data were collected through in-depth interviews, non-participant observations, and document analysis. Thematic analysis revealed that video production activities actively fostered values aligned with Islamic ethics, including discipline, responsibility, collaboration, and creativity. Students engaged not only with digital tools but also internalized moral lessons through scripting, directing, and reflecting on religious themes, such as honesty, patience, and communal accountability. While the initiative enhanced student engagement and self-confidence, it also encountered pesantren-specific challenges, such as time constraints due to tahfidz schedules, limited equipment, and the need for teacher training in media literacy. These findings highlight that integrating digital storytelling within pesantren pedagogy can serve as a transformative method for nurturing akhlÄq al-karÄ«mah (noble character) in line with Islamic educational ideals. This model offers new pathways for reimagining pesantren as centers of both religious integrity and technological adaptability.